The contribution of probiotics for the double-edge effect of cefazolin on postoperative neurocognitive disorders by rebalancing the gut microbiota - Zhang, Tianyao; Wu, Xiaochu; Liu, Bin; Huang, Han; Zhou, Cheng; Liang, Peng (Frontiers in Neuroscience, 2023)
Introduction Emerging data suggest that perioperative gut dysbiosis is prevalent and may be associated with postoperative neurocognitive disorders (PND). Antibiotics and probiotics are key factors influencing the microbiota. Many antibiotics have anti-microorganisms and direct anti-inflammatory properties, which may have cognitive repercussions. NLRP3 inflammasome activation has been reported to be involved with cognitive deficits. This study aimed to determine the effect and mechanism of probiotics on neurocognitive problems associated with perioperative gut dysbiosis by the NLRP3 pathway. Methods In a randomized, controlled trial, adult male Kunming mice undergoing surgery were administered cefazolin, FOS + probiotics, CY-09, or a placebo in four distinct experimental cohorts. Fear conditioning (FC) tests evaluate learning and memory. Following FC tests to evaluate inflammatory response (IR) and the permeability of barrier systems, the hippocampus and colon were extracted, and feces were collected for 16 s rRNA. Results One week after surgery, surgery/anesthesia decreased the frozen behavior. Cefazolin attenuated this declination but aggravated postoperative freezing behavior 3 weeks after surgery. Probiotics ameliorated surgery/anesthesia-induced memory deficits and perioperative cefazolin-induced postoperative memory deficits 3 weeks after surgery. NLRP3, caspase-1, Interleukin-1β (IL-1β), and Interleukin-18 (IL-18) levels were increased 1 week after the hippocampus and colon surgery, which were attenuated by CY-09 and probiotics, respectively. Discussion Probiotics could correct dysbacteria and IR caused by surgery/anesthesia stress and cefazolin alone. These findings imply that probiotics are an efficient and effective way of maintaining the balance of gut microbiota, which may reduce NLRP3-related inflammation and alleviate PND.